Rheumatoid pericarditis: New immunopathological aspects (1994)
Rheumatoid pericarditis (RP) is a well known extraarticular manifestation of rheumatoid arthritis (RA). It is not frequently diagnosed despite its high reported prevalence in post-mortem studies. There have been no immunohistological studies of its presence in pericardial membranes. Here we report a complete immunohistological study of two RA patients with RP complications, using a panel of monoclonal antibodies (mAbs) for the recognition of B, T, and NK cells. Both cases showed strong and almost exclusive pericardial membrane infiltration of CD8+ T-cells which was correlated with a higher than expected similar increase in the subset of peripheral blood lymphocytes (PBL). These findings suggest an important role for CD8+ T-cells in chronic RA, especially in this extraarticular manifestation of the disease.